Effect of capital structure, profitability and operational costs on corporate income tax payable - Hapsari, Yuni Puspo; Kuntadi, Cris (Gema Wiralodra, 2023)
Previous or relevant research is fundamental in a study or scientific article. Previous or relevant research strengthens the theory and phenomenon of the relationship or influence between variables. This article reviews the factors that affect corporate income tax payable, namely capital structure, profitability, and operating costs, a study of the Tax Accounting literature. This article aims to build a hypothesis on the influence between variables to be used in further research. This literature review article results are: 1) capital structure influences the corporate income tax payable; 2) profitability affects the corporate income tax payable; and 3) operating costs affect the Corporate Income Tax Payable.